2011
DOI: 10.1002/jbmr.375
|View full text |Cite
|
Sign up to set email alerts
|

Post–hip fracture use of prescribed calcium plus vitamin D or vitamin D supplements and antiosteoporotic drugs is associated with lower mortality: A nationwide study in Finland

Abstract: We previously found a positive association between calcium plus vitamin D and antiosteoporotic drugs and survival among hip fracture patients. Our aim was to verify this observation using a nationwide database. A retrospective cohort of home-discharged hip fracture patients aged 50 years or older (n ¼ 23,615) was enrolled from the national database. Primary exposure was medical treatment for osteoporosis, and the outcome was all-cause mortality. Cumulative mortalities were calculated using the Kaplan-Meier est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Risk factors for mortality after a hip fracture are higher age, male gender, comorbidity, cancer, functional inability and treatment with opiates, delayed surgery, major postoperative complications and use of assistive devices (Agusti et al 2012, Alegre-Lopez et al 2005, Maggi et al 2010, Paksima et al 2008. Bone medication (Agusti et al 2012, Nurmi-Luthje et al 2011 as well as calcium and vitamin D supplements (Nurmi-Luthje et al 2011) are associated with deceased mortality risk.…”
Section: Other Serious Consequences 222mentioning
confidence: 99%
“…Risk factors for mortality after a hip fracture are higher age, male gender, comorbidity, cancer, functional inability and treatment with opiates, delayed surgery, major postoperative complications and use of assistive devices (Agusti et al 2012, Alegre-Lopez et al 2005, Maggi et al 2010, Paksima et al 2008. Bone medication (Agusti et al 2012, Nurmi-Luthje et al 2011 as well as calcium and vitamin D supplements (Nurmi-Luthje et al 2011) are associated with deceased mortality risk.…”
Section: Other Serious Consequences 222mentioning
confidence: 99%
“…In a recent prospective study, predictors of long-term mortality in females with hip fracture were older age ([80 years) and dementia, and in males, correspondingly, were osteoporosis and older age ([80 years) [19]. During the last 10 years, some studies have shown an association between anti-osteoporotic treatment and reduced all-cause mortality [20,21].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, current national and international guidelines recommend the use of pharmacological treatments after hip fracture [10,11]. Moreover, the results of several studies showed a decreased mortality rate in patients who were managed with antiosteoporotic drugs as compared with those who were not [12][13][14]. In particular, in the HORIZON study [13] hip fracture patients were randomly assigned to receive annually zoledronic acid either by intravenous infusion or a placebo infusion; both groups received both oral calcium and vitamin D daily.…”
Section: Introductionmentioning
confidence: 99%